2018
DOI: 10.1002/zoo.21420
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of female cheetahs (Acinonyx jubatus) to urine volatiles from males of varying genetic distance

Abstract: Understanding the factors used by female cheetahs (Acinonyx jubatus) to make mate choice decisions could benefit zoo breeding programs, which currently assign mates based primarily on genetic distance. Because transporting animals between institutions is costly and can be stressful, females are often limited in the number of males available for mating. One solution would be to determine if an easily transported substance could be used to gauge interest by a female to a potential mate. Here, we investigate fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The females in our study spend 168 ± 97 (mean ± SD) seconds sniffing to both samples on the first day of the trial, which is only 14% of the time available. This is in line with other studies of solitary carnivores (Berzins & Helder, ; Mossotti, ). These results combined suggest that even shorter presentations of males’ urine and feces might be sufficient to measure a female preference.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The females in our study spend 168 ± 97 (mean ± SD) seconds sniffing to both samples on the first day of the trial, which is only 14% of the time available. This is in line with other studies of solitary carnivores (Berzins & Helder, ; Mossotti, ). These results combined suggest that even shorter presentations of males’ urine and feces might be sufficient to measure a female preference.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are supported to some extent by a study on another mustelid species, the domesticated ferret (Cloe, Woodley, Waters, Zhou, & Baum, ), which showed that a combination of volatile body odors, including anal scent gland secretions and urinary odors underlie olfactory sex discrimination and partner preference. Time spent sniffing is a common measure of preference in similar studies on cheetahs (Mossotti, ), rodents (Roberts, Davidson, Beynon, & Hurst, ), and primates (Fisher et al, ). Furthermore, approaching and proximity to odors have also been used as a measure of preference in studies of ferrets (Berzins & Helder, ; Cloe et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common scent preference protocols for (a) rodents in a dichotomous choice test using perforated tubing with soiled bedding inside (Zhang, Liang, Guo, & Zhang, ), (b) carnivores in a dichotomous choice test utilizing perforated tubing with gauze soaked in collected urine (Mossotti, Baskir, Kozlowski, Feldhamer, & Asa, ), and (c) carnivores with a multi‐scent presentation apparatus to identify cancerous cells which could easily be modified for mate preference (Pinc, Bartoš, Reslova, & Kotrba, ; Rothman, ).…”
Section: Applying Mate Choice In Species Survival Plans®mentioning
confidence: 99%
“…However, this protocol presents a challenge for institutions that lack facilities to house and manage a large number of males to serve as the breeding pool. Mossotti et al () presented male urine samples to female cheetahs (Figure a) and found that females approached and interacted with samples and tended to prefer those of males that were most genetically distant. To make this approach applicable to SSP® programs, the next step will be to determine whether the preferred urine sample predicts which male will be accepted for mating.…”
Section: Applying Mate Choice In Species Survival Plans®mentioning
confidence: 99%